Genetic diversity in the Velencei carp stock assayed by microsatellite markers - Keszte, Szilvia; Mészáros, Orsolya; Kánainé Sipos, Dóra; Balogh, Erna; Zellei, Ágnes; Sebestyén, András; Balogh, Réka; Guti, Csaba Ferenc; Bokor, Zoltán; Urbányi, Béla; Kovács, Balázs (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
In this study, we analysed the genetic composition of a separately developing carp stock, named as kosfejű carp („ram-headed” carp- Cyprinus carpio carpio morpha acuminatus) due to its phenotypic appearance, only found in the Lake Velence. To study the nuclear genomes of 36 carps, we used seven microsatellites supplemented with the results obtained from an earlier mitochondrial genome analysis. We isolated the genomic DNA from previously collected samples, carried out the PCR reactions suitable for detecting the alleles of microsatellite loci with the primer pairs (MFW7, MFW6, Cca02, Cca072, Koi41, MFW31, MFW26) specific to the loci of interest, then determined the lenght of the alleles with single-base-pair precision using capillary fragment analysis. Since the polymorphism of microsatellites is caused by allele-length changes, they are useful tools for the study of the genetic diversity of the stocks tested. During the course of the analysis, the observed heterozygosity (Ho), expected heterozygosity (He), and polymorphic information content (PIC) of the markers for given population were computed. Additionally, we tested the deviations from the Hardy-Weinberq equilibrium in the stock. The results of the microsatellite analysis showed that the stock deviated significantly in all locus, except Koi41-42 from the Hardy–Weinberg equilibrium and the estimated heterozygosity of the whole population is lower than expected. Most of the markers used in this study showed high polymorphism (MFW6, MFW7 Cca02, Cca072, MFW31, MFW26), therefore, are qualified for the analysis of the stock. Using more markers in the future will enable us to develop a cross design for raising genetic diversity. The work was supported by the European Fisheries Fund Fisheries Operative Program III. axis, European Fisheries Fund for Renewable Fisheries provided by the EU and Hungary.
Keywords: microsatellite; carp; diversity; genetics